PENGEMBANGAN MEDIA FLASH UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD KELAS IV SD HANGTUAH VI SURABAYA - Vit Ardhyantama (Alpen: Jurnal Pendidikan Dasar, 2019)
Learning media is a tool that can be used to support the achievement of learning objectives. Entering the industrial era 4.0, with the development of digital technology, all lines are required to adapt. Education area cannot be separated from that influence. Schools must have flexibility towards the times so that graduates can adapt and develop in society. Flash media is one solution that can be developed in implementing learning that is in line with the times. This study uses the 4D development method of Thiagarajan, Semmel, and Semmel (1974: 5). There are four stages in developing 4D, namely stage (1) Define; (2) Design (design); (3) Develop (development); and (4) Disseminate. The target of the study was fourth grade students at SD Hangtuah VI Surabaya. The development of producing flash media that is effective and efficient and successfully improves student learning outcomes.